Diversification, Growth, and Volatility in Asia - Papageorgiou, Chris; Spatafora, Nikola; Wang, Ke (World Bank, Washington, DC, 2015)
Economic development critically involves diversification and structural transformation—that is, the continued, dynamic reallocation of resources from less productive to more productive sectors and activities. This paper documents that, over an extended period, developing Asia has on average been particularly successful in diversifying its exports, particularly in comparison with Sub-Saharan Africa. Much of the progress has occurred through diversification along the ‘extensive margin,’ that is, through entry into completely new products. In addition, developing Asia has on average benefited significantly from quality upgrading, helping it capitalize on already existing comparative advantages. Yet, agricultural and natural resources tend to have lower potential for quality upgrading than manufactures. Therefore, for lower-income “frontier” countries, diversification into products with longer “quality ladders” may be a necessary first step before large gains from quality improvement can be reaped.